Pengaruh Kualitas Produk, Customer Trust, Dan Online Customer Rating Terhadap Keputusan Pembelian Di E-Commerce Shopee (Studi Pada Customer Shopee di Malang) - Dhimas Aji Prakoso; Budi Wahono; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine how the influence of Price Profitability, Service Quality and Promotion on Purchase Decisions for Shopee Food Delivery in Malang City. The population in this study were all shopee food application users in the city of Malang.This research uses quantitative data and the method of collecting it is by using a questionnaire via google form and measured by a Likert scale.. show Keywords : Product Quality, Customer Trust, And Online Customer